Language Variation - European Perspectives VIII : Selected Papers from the Tenth International Conference on Language Variation in Europe (ICLaVE 10), Leeuwarden, June 2019. - Van de Velde, Hans. (Studies in Language Variation Series, 2021)
Selected papers from the 10th International Conference on Language Variation in Europe, on language varieties ranging from Dutch-Frisian contact varieties to English in Sydney, Australia, and using quantitative and qualitative approaches to linguistic variables, state-of-the-art techniques for speech analysis, and new dialectometrical methods.